Apolipoprotein E (APOE) Genotype and Outcome in Infants with Hypoxic-Ischemic Encephalopathy (HIE) - Cotten, C. Michael (2013)
BACKGROUND: Adults with the apolipoprotein E gene (APOE) alleles e4 and e2 are at high risk of poor neurologic outcome after brain injury. The e4 allele has been associated with cerebral palsy and the e2 allele has been associated with worse neurologic outcome with congenital heart disease. This study was done to test the hypothesis that APOE genotype is associated with outcome among neonates who survive after hypoxic-ischemic encephalopathy (HIE). METHODS: We conducted a cohort study of infants who survived HIE and had 18 – 22 month standardized neurodevelopmental evaluations to assess associations between disability and APOE genotypes e3/e3, e4/-, and e2/- RESULTS: 139 survivors were genotyped. 86 (62%) were e3/e3, 41 (29%) were e4/-, and 14 (10%) were e2/-. 129 infants had genotype and follow-up data; 26% had moderate or severe disabilities. Disability prevalence was 30% and 19% among those with and without e3/e3 genotype, 25% and 26% among those with and without the e2 allele, and 18% and 29% among those with and without the e4 allele. None of the differences were statistically significant. Cerebral palsy prevalence was also similar among genotype groups. CONCLUSION: Disability was not associated with APOE genotype in this cohort of HIE survivors.